Hyperbaric oxygenation therapy in treatment of traumatic spinal cord injury: a pilot study - Nekhlopochyn, Oleksii S.; Voronov, Igor V.; Verbov, Vadym V. (Ukrainian Neurosurgical Journal, 2021)
Spinal cord traumatic injury as resulting persistent movement and sensory disorders is one of the most disabling consequences of traumatic factor impact on the human body. Despite a large number of experimental and clinical studies aimed at developing methods for restoring lost functions, there is no acceptable solution to the problem. One of the promising areas in the treatment and rehabilitation of this category of patients is the use of hyperbaric oxygenation (HBO). Experimental models have shown that HBO has a neuroprotective effect in spinal cord injury, but the results of clinical application of the method are still controversial. Objective: to determine the effectiveness of HBO in the complex therapy of victims with traumatic spinal cord injury and the feasibility of further study of this area. Materials and Methods: Study design is a pilot observational retrospective “case – control”. The database of patients with spinal cord injury who were hospitalized at Romodanov Neurosurgery Institute in the period from 2010 to 2020 were used for the analysis. When selecting a control for each clinical case, the following factors were considered: gender, age, circumstances of injury, type of damage to the osteoligamentous apparatus, level of neurological deficit, degree of damage and compression of the spinal cord, time elapsed from the moment of injury to surgery. 28 "case ‒ control" pairs were analyzed. The main criterion for therapy effectiveness was the change in the functional class according to the ASIA scale. Results. Positive dynamics was registered in 57% of victims, including in the group of patients receiving HBO therapy - in 71%, in the control group - in 43%. HBO therapy in the postoperative period significantly affects the dynamics of regression of neurological disorders (p=0.0295). The odds ratio is 3.333 (95% confidence interval - 1.098‒10.116, p=0.0335). The calculation of the odds ratio, adjusted for additional analyzed factors, showed a more pronounced efficiency - 4.519 (95% confidence interval - 1.279‒15.962, p=0.0192). Conclusions. The obtained results indicate that usage of HBO as a method of complex therapy for traumatic spinal cord injury is promising for further study in order to determine the effectiveness of the method, the optimal timing of treatment initiation in the postoperative period and its duration.